Traumatic Extremity Amputations in Children: Causes and Outcomes Based on a Regional Experience - Joyce J. L. H. McRae; Joseph Whitaker; Rebecca Dolman; Rosemary Vannix; Liang Ji; Andrei Radulescu; Donald Moores (Western Journal of Emergency Medicine, 2026)
Introduction: Pediatric traumatic extremity or digit amputations are preventable causes of morbidity. The object of this study was to evaluate the etiology and outcomes of these injuries in our region. We used the Childhood Opportunity Index to explore the role of social determinants of health. Methods: We performed a retrospective cohort study at an academic children’s hospital on all pediatric patients younger than 18 years who presented with a traumatic digit or extremity amputation between January 1, 2014, to July 31, 2024. Metrics such as patient demographics, injury severity, prehospital course, hospital events and follow-up were abstracted. The Childhood Opportunity Index assigns a 0-100 composite score of region-based childhood opportunity determined from home ZIP codes. Our primary outcome measure was mechanism of injury. Secondary outcomes included length of stay, need for initial surgical intervention, subsequent operations, or unplanned readmissions. Results: A total of 73 patients presented with a traumatic amputation of a digit or extremity. The median age was 12.7. The top three causes of amputations were all-terrain vehicle (ATV) crashes, fireworks, and entrapment in an object. All-terrain vehicle crashes were the most common cause in all age groups from 5-17, while caught in an object was the most common for ages 0-4. The median Injury Severity Score was 5 (IQR 7). The three most common sites of amputation were right index finger (21), right long finger (17), and left long finger (15). Thirty-three children (45.2%) had more than one amputation. The highest number of amputations in a single patient was 10. All patients underwent a surgical intervention, and there were no mortalities. The median Childhood Opportunity Index score of the cohort was low at 19 (IQR 33), with 73% (n = 53) of the cohort originating from a very low (n = 37) or low (n = 16) index region. A rising index score was weakly associated with a decrease in total number of amputations (ρ = -0.25 [CI, -0.45 to -0.02, P = .04]). Conclusion: A. total of 73 children in our region suffered a traumatic digit or extremity amputation, mostly due to ATV crashes and fireworks. Most patients originated from a neighborhood of very low or low Childhood Opportunity Index scores. Increased public awareness regarding the danger of ATVs in regions with lower index scores may prevent these injuries. Clear, targeted policies toward ATV usage in childhood are needed.